Self-sufficiency and sustainable cities and regions : planning for sustainable, circular and carbon-neutral development - Medeiros, Eduardo (Geography professor) (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The concept of Self-Sufficiency involves the notion of sustainable, circular, and carbon-neutral cities. This book examines how urban planning can lead to greater self-sufficiency. It sheds light on how Urban and Regional Circular and Self-Sufficiency development can effectively contribute towards the ultimate goals of the United Nations (UN) Agenda 2030 and the European Union (EU) Green Deal. It embraces not only the scientific fields of regional and urban studies but also addresses environmental sustainability-related and regional resilience aspects, such as renewable energy production, sustainable mobility, and the circular economy. The book offers a full toolkit of knowledge on how to effectively implement planning approaches for circular and self-sufficiency development at both urban and regional levels. It begins by presenting a theoretical framework and debate on urban and regional planning approaches that can effectively make cities and regions circular and self-sufficient in certain development domains, such as producing intra-city electric energy, sustainable mobility, and promoting a circular economy. Further, it advances a range of policy development proposals aiming at providing a comprehensive introduction to contemporary thinking about how cities and regions can design innovative planning and governance processes and, where appropriate, build capacity to implement systemic and integrated climate-neutral policies, building on existing place-based territorial capital and experiences developed by local and regional networks. The chapters are written by established authors in their respective domains. The book will thoroughly prepare students and provide knowledge to academics, researchers, and policymakers in the fields of urban and regional planning/development and studies, environmental sustainability, regional resilience, human geography, economic development, and public/EU/UN policies"--
Keywords: Sustainable urban development; Regional planning -- Environmental aspects; Sustainable development; BUSINESS & ECONOMICS / Urban & Regional; BUSINESS & ECONOMICS / Development / Sustainable Development; BUSINESS & ECONOMICS / Development / Economic Development